Proximal feed artery regulation of skeletal muscle blood flow during exercise : the paraplegic model - Scriba, E. W. (Ernst Wolfgang) (Stellenbosch : Stellenbosch University, 2012)
Assignment (MPhil)--University of Stellenbosch, 2003.